How much to say or do? : an exploration from a public journalism perspective on the community involvement of the West Coast commercial community newspaper Weslander - Meissenheimer, Helene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2006.